THE ROLE OF E-COMMERCE IN MEDIATING CONSUMER LOYALTY AND BRAND AWARENESS ON PURCHASING DECISIONS ON WARDAH PRODUCTS - Aprilianingsih; Noorjaya Nahan; Ina Karuehni (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective –  This research aims to determine the role of e-commerce in mediating consumer loyalty and brand awareness on purchasing decisions. Design/Methodology/Approach – The type of research used in this research is quantitative. The population and sample used in this research were Wardah product users among students at the Faculty of Economics and Business, Palangka Raya University. The number of respondents was 126 people using the Ferdinand formula. The data scale used in this research is a five (5) point odd Likert scale. The analytical tool used in this research is Partial Least Square (PLS) with a Structural Equation Modeling (SEM) approach. Findings – The research results show that consumer loyalty and brand awareness has a positive significant effect on Wardah product e-commerce and purchasing decisions. E-commerce has a positive and significant effect on purchasing decisions. Consumer loyalty and brand awareness has a positive and significant effect on purchasing decisions through e-commerce for Wardah products among students at the Faculty of Economics and Business, Palangka Raya University. Conclusion and Implications – E-commerce can fully mediate between consumer loyalty and brand awareness in purchasing decisions. Wardah company can increase sales by improving service to consumers in order to increase consumer loyalty and consumer brand awareness through improving e-commerce services.